Optimalisasi Hasil Belajar IPA Berbasis Problem Based Learning (PBL) Melalui Lesson Study - Amrilizia, Nassa; Yusro, Andista Candra; Tamami, Muhammad Dafiq (Universitas Sarjanawiyata Tamansiswa, 2023)
The role of the science teacher in the learning process is as a facilitator in achieving learning objectives. Teachers are involved in the process of planning, implementing and reflecting. This is a challenge for teachers in managing their classes and enhancing their professional identity. Implementation of lesson study can be used as an alternative for school-based teacher professional development so as to improve the performance of science learners. This research is a classroom action research by implementing the Problem Based Learning (PBL) learning model through lesson study with the stages of plan, do see. This research collaborated with 4 PPG students and science expert teachers. Student learning outcomes show that 75% of students complete above KKM 75 so that there are only 25% of other students who have not completed. However, the results of the percentage of students' classical completeness only reached 63% so that in one class they had not achieved optimal learning mastery.